2021
DOI: 10.1039/d0ob02190c
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Pro-Hyp-Gly provides 2 kcal mol−1 stability but attenuates the specific assembly of ABC heterotrimeric collagen triple helices

Abstract: Collagen is a major structural component of the extracellular matrix and connective tissue. The key structural feature of collagen is the collagen triple helix, with a Xaa-Yaa-Gly (glycine) repeating pattern....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Collagen model peptides (CMPs) with Pro‐Hyp‐Gly repeats have hence been used as synthetic surrogates. [1] These peptides consist typically of 20–40 amino acids and are useful for studying the factors that affect the stability[ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and the dynamics[ 20 , 21 , 22 , 23 , 24 ] of the collagen triple helix. Such studies revealed, for example, the importance of steric and stereoelectronic effects, interstrand H‐bonding, hydrophobicity, and PPII helicity of the individual strands for collagen triple helix stability.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen model peptides (CMPs) with Pro‐Hyp‐Gly repeats have hence been used as synthetic surrogates. [1] These peptides consist typically of 20–40 amino acids and are useful for studying the factors that affect the stability[ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and the dynamics[ 20 , 21 , 22 , 23 , 24 ] of the collagen triple helix. Such studies revealed, for example, the importance of steric and stereoelectronic effects, interstrand H‐bonding, hydrophobicity, and PPII helicity of the individual strands for collagen triple helix stability.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen model peptides (CMPs) with Pro-Hyp-Gly repeats have hence been used as synthetic surrogates. [1] These peptides consist typically of 20-40 amino acids and are useful for studying the factors that affect the stability [7][8][9][10][11][12][13][14][15][16][17][18][19] and the dynamics [20][21][22][23][24] of the collagen triple helix. Such studies revealed, for example, the importance of steric and stereoelectronic effects, interstrand H-bonding, hydrophobicity, and PPII helicity of the individual strands for collagen triple helix stability.…”
Section: Introductionmentioning
confidence: 99%